Abrasive Articles and Methods for Forming Same
Patent Information
- Application Number
- JP2022172639
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2014-12-30
- Filing Date
- 2022-10-27
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2035-12-30
Smart Images

Figure 0007611884000003 
Figure 0007611884000004 
Figure 0007611884000005
Abstract
Description
[Technical field]
[0001] The present invention relates generally to abrasive articles, and in particular to abrasive articles comprising nanocrystalline alumina. This is regarding. [Background technology]
[0002] The abrasive article may include abrasive particles contained in a bond matrix. Some types of abrasive particles, such as alumina, may be susceptible to chemical reactions at high temperatures. Glass The binder tends to penetrate and react with the microcrystalline alumina grit during high temperature formation of the abrasive article. This can reduce the hardness of the abrasive and even lead to corrosion of the abrasive. do.
[0003] There is a continuing need in the industry for improved abrasive articles. [Brief description of the drawings]
[0004] Embodiments are illustrated by way of example and not limitation in the accompanying figures.
[0005] [Figure 1] FIG. 1 includes a flow chart for forming an abrasive article. [Diagram 2] FIG. 1 includes a perspective view of a shaped abrasive particle according to one embodiment. [Diagram 3] FIG. 1 includes a perspective view of a shaped abrasive particle according to one embodiment. [Figure 4] FIG. 1 includes a perspective view of a shaped abrasive particle according to one embodiment. [Diagram 5] FIG. 1 includes a perspective view of a shaped abrasive particle according to one embodiment. [Figure 6A] FIG. 1 includes an SEM image of conventional microcrystalline alumina grains. [Figure 6B] FIG. 1 includes SEM images of nanocrystalline alumina grains according to one embodiment. [Figure 7A]FIG. 1 includes plots of modulus of rupture for abrasive samples. [Figure 7B] FIG. 1 includes plots of elastic modulus of abrasive samples. [Figure 8] FIG. 1 includes plots of force thresholds for abrasive samples.
[0006] Those skilled in the art will appreciate that elements in the figures have been illustrated for simplicity and clarity, and are necessarily Please be aware that the drawings are not necessarily to scale. For example, some of the elements in the drawings may be Some dimensions are shown in comparison with other elements to aid in a better understanding of the embodiments of the present invention. There are some things that are emphasized. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] The following description in conjunction with the figures is provided to aid in understanding the teachings disclosed herein. The following discussion focuses on specific implementations and embodiments of the present teachings. This emphasis is provided to aid in the explanation of the teachings and is intended to clarify the scope of the teachings. This document should not be construed as limiting or limiting the scope of this application. Certainly other teachings can be used in the present invention.
[0008] As used herein, "comprises" and "including" are used interchangeably herein. "including", "includes", "including The terms "has", "having" or "having" Any other variations thereof are intended to be encompassed without limitation. For example, a method, article, or apparatus that includes recited features is not necessarily limited to only those features. and does not include any other features or inherent features of these methods, articles, or apparatus not expressly recited. Moreover, unless expressly stated to the contrary, To the extent that "or" means an inclusive "or" and not an exclusive "or," For example, condition A or B is satisfied by one of the following: A is true and ( or exists) and B is false (or does not exist), A is false (or does not exist) ) and B is true (or exists), and both A and B are true (or exist). (I).
[0009] Also, "a" or "an" refers to any element described herein. and ingredients are used in the description of the compositions. This is done merely for convenience and to provide a general understanding of the scope of the invention. This description should be interpreted as including one or at least one. and unless a clearly different intention exists, the singular includes the plural and the plural the singular. For example, when one embodiment is described in this specification, one embodiment is also included. Instead of a form, more than one embodiment may be used. Where more than one embodiment is described, the more than one embodiment is referred to as a single It may be replaced by the embodiment.
[0010] Unless otherwise specified, all technical and scientific terms used herein are understood to be those of the The term "material" has the same meaning as commonly understood by a person skilled in the art to which the invention pertains. The methods and examples are illustrative only and are not intended to be limiting. To the extent that specific details regarding processing activities are not provided, such details will be provided in accordance with the Conventional approaches may include those described in reference books and other sources in the manufacturing arts. It may also be found in
[0011] An embodiment is a method of forming an abrasive article, comprising: and heating the mixture to a forming temperature to form an abrasive article. The method further comprises forming an abrasive article having improved performance. may be facilitated.
[0012] FIG. 1 includes a flow chart of a method of forming an abrasive article according to one embodiment. In step 101, a binder (or a precursor of the binder) and abrasive grains including nanocrystalline alumina are mixed. A mixture containing the polymer and the cellulose can be prepared. The mixture can be wet or dry. The binder may be in the form of a powder material that can be mixed with the abrasive particles. In certain instances, suitable mixing procedures may be used to uniformly disperse the ingredients within the mixture. can be done.
[0013] The mixture may also contain one or more additives, including, for example, a second abrasive particle and a filler. According to a non-limiting embodiment, the second abrasive particles may be aluminum oxide. Na, silicon carbide, cubic boron nitride, diamond, flint, and garnet grains; and any combination thereof. In another non-limiting embodiment, Some suitable filler materials include organic and inorganic materials. The filler may be different from the particles. For example, the filler may be hollow glass beads, crushed walnut shells, beads of plastic materials or organic compounds, foam glass particles, and foam a The pore formers include lumina, elongated grains, fibers, and combinations thereof. Other filler materials include pigments and / or dyes, fibers, woven materials, non-woven materials, Particles, spheres, minerals, nuts, shells, oxides, alumina, carbides, nitrides, borides, organic materials The materials may include materials, polymeric materials, naturally occurring materials, powders, and combinations thereof. In one embodiment, the filler may be a powder, a granule, a sphere, a fiber, a pore former, a hollow particle, and the like. In certain embodiments, the filler may be selected from the group consisting of the compounds of the present invention. The composition may consist essentially of any one of the materials described herein. wherein the filler consists essentially of two or more of the materials described in the embodiments herein. It is possible.
[0014] After the mixture is formed in step 101, the process can continue with step 102. Step 102 heat treats the mixture to form nanocrystals contained in a three-dimensional network of the binder. forming an abrasive article in the form of a wheel body having abrasive particles comprising reactive alumina. It is possible to do so.
[0015] According to one embodiment, the mixture can be heat treated to a forming temperature. 00° C. or higher, for example 950° C. or higher, or 975° C. or higher. According to an embodiment, the formation temperature is 1200° C. or less, for example, 1175° C. or less, 1150° C. or less, 11 The formation temperature of the embodiments herein may be 25° C. or less, or 1100° C. or less. The abrasive particles provide enough heat to bond with the binder, but the specific material contained in the binder is It can help reduce reactivity.
[0016] According to another embodiment, the binder may include inorganic materials such as ceramics. A ceramic material is a composition that contains at least one metal or metalloid element. Metal or semimetal elements include alkali metal elements, alkaline earth metal elements, lanthanide, These include, but are not limited to, oxides, transition metal elements, and combinations thereof. The cou materials may include oxides, carbides, nitrides, borides, and combinations thereof. Additionally, ceramic materials include single crystalline phases, polycrystalline phases, amorphous phases, and combinations thereof. Ceramic materials can consist essentially of single crystalline, polycrystalline, or amorphous phases. It will be understood that this is possible.
[0017] According to another embodiment, the bonding material can include a glass material. For example, the binder may consist essentially of a glass material having an amorphous phase. According to yet another embodiment, the bonding material may include a non-glass material. The non-glass material may include a polycrystalline phase. The material may include a mixture of polycrystalline and glass materials.
[0018] According to at least one embodiment, the binder improves the formation and / or performance of the abrasive article. It can contain a certain content of boron oxide (B2O3) which can facilitate the improvement of The boron oxide may be present in a specific weight percentage relative to the total weight of the binder. For example, boron oxide is 30% by weight or less, for example, 28% by weight or less, 26% by weight or less, 2 In another example, the binder may be 5% by weight or less, or even 22% by weight or less. % by weight or more, for example 8% by weight or more, 10% by weight or more, 12% by weight or more, or even 1 It may contain 5% by weight or more of boron oxide. The weight percentage of boron oxide in the binder The percentages range from the lowest percentage listed above to the highest percentage listed above. For example, the binder may be in the range of 5% by weight to 30% by weight. The boron oxide may be present in the range of 8% by weight to 22% by weight.
[0019] In another embodiment, the binder facilitates formation and / or improves the performance of the abrasive article. The binder may contain a specific content of silicon oxide (SiO2). The content of silicon oxide relative to the total weight is, for example, 80% by weight or less, 75% by weight or less, 70% by weight or less, % by weight or less, 65% by weight or less, 55% by weight or less, 52% by weight or less, or even 50% by weight or less In another embodiment, the binder may be 25% by weight or more, for example 30% by weight or less. % or more, 35% or more, 38% or more, or even 40% or more by weight of ketone oxide. The silicon oxide content shall be the minimum of any of the percentages listed above. It will be understood that the range may be from 0.01 to any maximum percentage. For example, the content of silicon oxide is within the range of 35% by weight to 80% by weight, or 40% by weight to 65% by weight. In certain embodiments, the silicon oxide content can be in the range of , may be within the range of 40% by weight to 50% by weight.
[0020] In certain embodiments, the binder facilitates formation and / or improves the performance of the abrasive article. The oxide may contain a specific content of boron oxide and silicon oxide. The total content of boron and silicon oxide is 80% by weight or less, for example, 77% by weight or less, 75% by weight or less % or less, 73% or less, 70% or less, or even 65% or less by weight. In another embodiment, the total content of boron oxide and silicon oxide is 40% by weight or more, 42% by weight or more, 46% by weight or more, 48% by weight or more, or even 50% by weight or more. The total content of boron oxide and silicon oxide can be within the range of the maximum content disclosed in this specification. The range can be between one of the smallest and one of the largest percentages. For example, the total content of boron oxide and silicon oxide is 40% by weight to 80% by weight. % by weight, or in the range of 42% to 77% by weight, or in the range of 46% to 73% by weight or in the range of 50% to 65% by weight.
[0021] In certain instances, the binder facilitates formation and / or improves the performance of the abrasive article. The binder may have a specific ratio of boron oxide to silicon oxide. The silicon oxide and boron oxide may have a weight percentage ratio of silicon oxide to boron oxide, The percentage ratio should be 5.5:1 (SiO2:B2O3) or less, e.g. 5.2:1 or less, 5: 1 or less, or even 4.8:1 or less. In another example, silicon oxide and The weight percent ratio of boron oxide is 1:1 or more, 1.3:1 or more, 1.5:1 or more, 1. It can be 7:1 or more, 2.0:1 or more, or even 2.2:1 or more. The weight percent ratio of silicon to boron oxide may be any of the minimum and maximum ratios listed above. It will be understood that the ratio may be within any range. For example, the ratio may be 1:1 to 5.5. :1, or within the range of 1.5:1 to 5.2:1, or 1.8:1 to 5 / 0:1 or in the range of 2.2:1 to 4.8:1.
[0022] According to one embodiment, the bond facilitates formation and / or improves the performance of the abrasive article. The total content of the binder may include aluminum oxide (Al2O3). The content of aluminum oxide by weight is 31% by weight or less, for example 28% by weight or less, It may be 5% by weight or less, 23% by weight or less, or even 20% by weight or less. In terms of form, the content of aluminum oxide in the binder is 5% by weight or more, 8% by weight or less. % or more, 10% or more, 12% or more, or even 14% or more. The aluminum oxide content may be any of the minimum and maximum percentages listed above. It will be understood that the range of the composition may be any of the ranges of the compositions, for example, aluminum oxide. The content of the rubber is within the range of 5% to 31% by weight, or within the range of 10% to 25% by weight. It can be said that:
[0023] According to at least one embodiment, the binder provides improved and / or improved performance in forming the abrasive article. The composition may contain aluminum and alumina in amounts that can facilitate improved performance. For example, the binder may contain 15% by weight or more of alumina and aluminum metal (A In yet another example, the binder may comprise a total of 1203 / Al. 18% or more by weight, for example 20% or more, 22% or more, or even 24% or more by weight It may contain more than 100% by weight of alumina and aluminum metal (Al2O3 / Al). In a non-limiting embodiment, the binder comprises 45% by weight or less of the total weight of the binder, for example 4 2% by weight or less, 40% by weight or less, 38% by weight or less, 35% by weight or less, or even 32% by weight or less The binder may contain up to 50% by weight of alumina and aluminum metal. Alumina content within the range including either percent of or maximum percent of It will be appreciated that the present invention may include, for example, alumina and aluminum metal. The content of the minium metal is within the range of 5% by weight to 45% by weight, or 10% by weight to 40% by weight. %, or in the range of 22% to 35% by weight.
[0024] In one embodiment, the binder may include aluminum oxide and silicon oxide. For example, the total content of aluminum oxide and silicon oxide in the total weight of the binder is 5 0% by weight or more, for example 52% by weight or more, 56% by weight or more, 58% by weight or more, or even In another embodiment, the amount of aluminum oxide and the amount of acid may be 60% by weight or more. The total content of silicon dioxide is 80% by weight or less, 77% by weight or less, 75% by weight or less, or The total content of aluminum oxide and silicon oxide may be 73% by weight or less. The percentages may be within the range of any of the following minimum and maximum percentages: For example, the total content may be within the range of 50% by weight to 80% by weight. , in the range of 56% to 75% by weight, or even in the range of 60% to 73% by weight. It is possible.
[0025] In certain instances, silicon oxide and aluminum oxide are useful in forming abrasive articles and / or can be present in a particular weight percentage ratio that can facilitate improved performance. The weight percentage ratio of silicon oxide:aluminum oxide (SiO2:Al2O3) is, for example, For example, it may be 2.5:1 or less, such as 2.2:1 or less, or even 2:1 or less. In the example, the weight percent ratio of silicon oxide to aluminum oxide is 1:1 or more, 1 It may be 1.3:1 or more, 1.5:1 or more, or even 1.7:1 or more. The weight percent ratio of silicon dioxide to aluminum oxide is between one of the minimum ratios listed above and a maximum ratio of It will be understood that the ratio may be within any range. For example, the ratio may be 1:1 It may be in the range of 1.3:1 to 2.2:1.
[0026] According to at least one embodiment, the binder improves the formation and / or performance of the abrasive article. At least one alkaline earth oxide compound (RO) having a content capable of facilitating improvement The total content of alkaline earth oxide compounds relative to the total weight of the binder. may be 3.0% by weight or less, 2.5% by weight or less, or 2% by weight or less. In terms of form, the total content of alkaline earth oxide compounds (RO) is 0.5% by weight or more. or 0.8% by weight or more. is within the range from one of the minimum percentages to one of the maximum percentages listed above. For example, the total content may be 0.5% by weight to 3.0% by weight. %, or in the range of 0.8% to 2.5% by weight.
[0027] In certain embodiments, the alkaline earth oxide compound is calcium oxide (CaO). , magnesium oxide (MgO), barium oxide (BaO), or strontium oxide ( In a further embodiment, the binder may include more than three different types of binder. For example, the binder may not contain any alkaline earth oxide compounds such as calcium oxide. Three oxides selected from the group consisting of aluminum oxide, magnesium oxide, barium oxide, and strontium oxide. The composition may be free of more than two different alkaline earth oxide compounds.
[0028] According to another embodiment, the binder facilitates formation and / or improves the performance of the abrasive article. The calcium oxide (CaO) content may be: The binder content is 0.5% by weight or more, for example 0.8% by weight or more, or 1% by weight or more of the total weight of the binder. In yet another embodiment, the calcium oxide content is 3% by weight. or less, for example, 2.8% by weight or less, 2.5% by weight or less, 2% by weight or less, or 1.7% by weight or less The content of calcium oxide compounds may be less than or equal to any of the above minimum percentages. It will be understood that the range can be anywhere from this to a maximum percentage. For example, the total content is within the range of 0.5% by weight to 3.0% by weight, 0.8% by weight to 2.5% by weight %, or in the range of 1% to 1.7% by weight.
[0029] According to another embodiment, the bond may include an alkali oxide compound (RO). Exemplary alkali oxide compounds include lithium oxide (Li2O), sodium oxide (Na2O4), and sodium phosphate (Al2O4). (Na2O), potassium oxide (K2O), or cesium oxide (Cs2O). In a further embodiment, the binder may comprise at least one alkali oxide compound. In particular, the alkali oxide compounds include lithium oxide (Li2O), Sodium oxide (Na2O), potassium oxide (K2O), cesium oxide (Cs2O), and The compound may be selected from a group consisting of combinations thereof.
[0030] According to another embodiment, the total content of the alkali oxide compounds relative to the total weight of the binder is , 25% by weight or less, 22% by weight or less, or 20% by weight or less. The total content of alkali oxide compounds is 3% by weight or more, 5% by weight or more, 7% by weight or more, or The total content of the alkali oxide compounds may be 9% by weight or more. The range may be from one of the smallest percent to one of the largest percent. It will be understood that the range can be, for example, within the range of 3% by weight to 25% by weight. Or, the range of 7% by weight to 22% by weight may be mentioned.
[0031] For example, the binder may facilitate formation and / or improve the performance of the abrasive article. The lithium oxide (Li2O) content is based on the total weight of the binder. The content of thium is 1% by weight or more, for example 1.5% by weight or more, or 2% by weight or more. In another example, the lithium oxide content is 7% by weight or less, 6.5% by weight or less. % or less, 6% or less, 5.5% or less, or 5% or less by weight. The content of aluminum may range from one of the minimum percentages to one of the maximum percentages listed above. It will be understood that the range of the amount of the amine may be within a range of, for example, 1% by weight. In another embodiment, the range is from 1.5% to 7% by weight, or from 1.5% to 6% by weight. In some cases, the binder may contain trace amounts of Li2O or may be essentially free of Li2O. stomach.
[0032] In another embodiment, the binder may facilitate formation and / or improve the performance of the abrasive article. The binder may contain sodium oxide (Na2O) in an amount sufficient to achieve the above. The content of sodium oxide is, for example, 3% by weight or more, 4% by weight or more, or 5% by weight or more. In another example, the sodium oxide content may be 14% by weight or less, e.g. For example, it may be 13% by weight or less, 12% by weight or less, 11% by weight or less, or 10% by weight or less. The sodium oxide content may vary from any of the minimum percentages listed above to the maximum percentage. It will be understood that the range may be anywhere from 1 to 100%. For example, the range is 3% by weight to 14% by weight, or 4% by weight to 11% by weight. can be.
[0033] In another embodiment, the binder facilitates formation and / or improves the performance of the abrasive article. The binder may contain a content of potassium oxide (K2O) that can be used for example. The content of potassium oxide in the total weight is 1% by weight or more, 1.5% by weight or more, or double In at least one non-limiting embodiment, the amount of potassium oxide is 100% or more. The content is 7% by weight or less, for example, 6.5% by weight or less, 6% by weight or less, 5.5% by weight or less, The potassium oxide content may be less than or equal to 5% by weight. It is understood that the range can be from any to any maximum percent. The range may be, for example, 1% by weight to 7% by weight, or 1.5% by weight to 6.5% by weight. The range of % by volume is included.
[0034] In certain embodiments, the binder facilitates formation and / or improves the performance of the abrasive article. The binder may contain a phosphorus oxide (P2O5) content that can be adjusted to 100%. The total content of phosphorus oxides relative to the total weight is 3.0% by weight or less, for example 2.0% by weight or less; In certain embodiments, the binder may contain phosphorus oxide or less. It does not necessarily have to be essentially absent.
[0035] According to one embodiment, the bond comprises a composition that is essentially free of certain oxide compounds. For example, the binder can be TiO2, Fe2O3, MnO2, ZrSiO2, Co A composition essentially free of oxide compounds selected from the group consisting of Al2O4 and MgO. It can contain things.
[0036] According to at least one embodiment, the abrasive particles are nanoparticles having a particular average crystallite size. For example, the average crystallite size of the nanocrystalline alumina particles may be The size is 0.15 microns or less, for example 0.14 microns or less, 0.13 microns or less, or 0.12 microns or less, or even 0.11 microns or less. In embodiments, the average crystallite size is 0.01 microns or more, for example 0.02 microns or more. 0.05 microns or more, 0.06 microns or more, 0.07 microns or more, 0.0 The average crystallite size can be greater than 8 microns, or greater than 0.09 microns. and may be within a range from any of the minimum values to any of the maximum values mentioned above, inclusive. For example, the average crystallite size is 0.01 microns to 0.15 microns. 0.05 microns to 0.14 microns or 0.07 microns to 0.14 microns range In certain embodiments, the crystallite size can be within 0.08 microns. The thickness can be in the range of 0.1 to 0.14 microns.
[0037] The average crystallite size was determined using scanning electron microscope (SEM) micrographs with uncorrected inversion. The measurement can be based on the Tercept method. A sample of polished grains is placed in an epoxy resin. After making the Bakelite mount, polishing with Struers Tegramin 30 The unit is polished with diamond polishing slurry. After polishing, the epoxy is heated on a hot plate and then polished. The surface is thermally etched at 150°C for 5 minutes, which is below the sintering temperature. The coarse grains were mounted on an SEM mount and then gold-coated for SEM preparation. SEM micrographs of three separate abrasive particles were taken at approximately 50,000x magnification and then The following steps are used to calculate the uncorrected crystallite size: 1) From one corner of the crystal structure to the opposite corner Draw a diagonal line around the bottom of the photograph, excluding the black data band (e.g., Figures 7A and 7B). 2) The lengths of the diagonals L1 and L2 are measured to the nearest 0.01 centimeter. Measure and round to the nearest whole number; 3) The number of grain boundaries that each diagonal line crosses (i.e., the grain boundary intersections). Count the differences I1 and I2) and record this number for each diagonal; 4) for each micrograph or the length of the micron bar (in centimeters) at the bottom of the diagram screen (i.e. "bar Measure the length of the bar (in microns) by the length of the bar (in centimeters) 5) Divide the diagonal of the photomicrograph to determine the calculated bar number. Add the total centimeters (L1+L2) to get the total length of the diagonals;6) Add the number of grain boundary intersections of the square wire (I1 + I2) to get the total grain boundary intersections; 7) The sum of the diagonal lengths in meters (L1+L2) is the sum of the grain boundary intersections (I1+I2 ) and multiply this number by the calculated value of the bar number. This process is The average crystallite size is obtained by performing at least three separate runs on three different samples.
[0038] As an example of how to calculate the bar number, suppose the bar shown in the photo has a length of 0.4 microns. Assume that the length of a bar measured in centimeters using a ruler is 2 cm. Dividing the bar length, 0.4 microns, by 2 cm gives the calculated bar number of 0. 2um / cm. The average crystallite size is the sum of the diagonal lengths in centimeters. Divide (L1+L2) by the sum of grain boundary intersections (I1+I2) and add this number to the bar number. Multiply the calculated value.
[0039] According to one embodiment, the nanocrystalline alumina comprises 51% or more by weight based on the total weight of the abrasive particle. For example, the content of alumina in the nanocrystalline alumina can be About 60% by weight or more, 70% by weight or more, 80% by weight or more, about 85% by weight or more, or even or more, for example, 90% by weight or more, 92% by weight or more, 93% by weight or more, or 94% by weight or more In one non-limiting embodiment, the alumina content can be: 99.9% by weight or less, for example 99% by weight or less, 98.5% by weight or less, 98% by weight or less, 7.5% by weight or less, 97% by weight or less, 96.5% by weight or less, or 96% by weight or less The alumina content may be any of the minimum percentages listed above to the maximum percentages listed above. It will be understood that the range may include any of the above. For example, the content is within the range of 60% by weight to 99.9% by weight, 70% by weight to 99% by weight, 85% by weight % to 98% by weight, or in the range of 90% to 96.5% by weight. In certain embodiments, the single crystal alumina is essentially alumina, such as alpha alumina. It may be made of alumina.
[0040] As described herein, nanocrystalline alumina has many specific characteristics. These characteristics may apply to abrasive particles as well. For example, the abrasive particles may be The alumina content in relation to the total weight of the abrasive particles is similar to the alumina content in relation to the total weight of the nanocrystalline alumina. For example, the abrasive grains may include alumina in an amount of about 100% by weight. The content of alumina in the total weight of the ceramics is 60% by weight or more, for example, 70% by weight or more, 80% by weight or more. % by weight or more, 85% by weight or more, 90% by weight or more, 92% by weight or more, 93% by weight or more, In another example, the content of alumina in the abrasive particles may be 94% by weight or more. is 99.9% by weight or less, for example, 99% by weight or less, 98.5% by weight or less, 98% by weight or less , 97.5% by weight or less, 97% by weight or less, 96.5% by weight or less, or 96% by weight or less The abrasive particles may be present in amounts within the range of the minimum and maximum percentages set forth above. It will be understood that the alumina content can be, for example, 60% by weight to 50% by weight. Within the range of 99.9% by weight, within the range of 70% by weight to 99% by weight, or within the range of 85% by weight to 98% by weight The range may be within the range of 90% to 96.5% by weight. In some embodiments, the abrasive particles consist essentially of alumina, such as alpha alumina. It is possible.
[0041] According to one embodiment, the nanocrystalline alumina may include at least one additive. Additives include transition metal elements, rare earth elements, alkali metal elements, and alkaline earth metal elements. In a further embodiment, the additive may include, for example, silicon, or a combination thereof. Additives include transition metal elements, rare earth elements, alkali metal elements, alkaline earth metal elements, silicon, and combinations thereof. It is understood that the additives described in the embodiments can be applied to the abrasive particles. In one embodiment, the abrasive particles contain one or more of the additives described herein. can include more than one.
[0042] In another embodiment, the additive is, for example, magnesium, zirconium, calcium , silicon, iron, yttrium, lanthanum, cerium, or a combination thereof. In a further embodiment, the additive may include magnesium, zirconium, selected from the group consisting of yttrium, calcium, silicon, iron, yttrium, lanthanum, and cerium; The nanocrystalline alumina may include two or more materials selected from alumina and one ... It will be appreciated that the abrasive particles may consist essentially of, or consist of, a combination of, or a combination of the above additives. can consist essentially of alumina and one or more of the additives described above. will also be understood.
[0043] According to one embodiment, the total content of the additives relative to the total weight of the nanocrystalline alumina particles is , 12% by weight or less, for example 11% by weight or less, 10% by weight or less, 9.5% by weight or less, 9% by weight or less % or less, 8.5% by weight or less, 8% by weight or less, 7.5% by weight or less, 7% by weight or less, 6.5% by weight % or less, 6% by weight or less, 5.8% by weight or less, 5.5% by weight or less, or 5.3% by weight or less In another embodiment, the total content of the additives is , 0.1% by weight or more, for example 0.3% by weight or more, 0.5% by weight or more, 0.7% by weight or more, 1% by weight or more, 1.3% by weight or more, 1.5% by weight or more, or 1.7% by weight or more, 2% by weight or more % or more, 2.3% or more, 2.5% or more, 2.7% or more, or even triple The total content of the additives in the nanocrystalline alumina can be the above-mentioned maximum content. The range shall be between the smallest percent and the largest percent, inclusive. For example, the total content may be in the range of 0.1% by weight to 12% by weight. For example, within the range of 0.7% to 9.5% by weight, or 1.3% to 5.3% by weight The total content of the additives relative to the total weight of the abrasive particles can be within the range of It is also understood that the embodiments described herein may include similar percentages or ranges. Let's do it.
[0044] In one embodiment, the additives facilitate the formation and / or improve the performance of the abrasive article. The content of magnesium oxide (MgO) can be as high as 100%. The content of magnesium oxide relative to the total weight of lumina is, for example, 0.1% by weight or more, e.g. 0.3% by weight or more, 0.5% by weight or more, 0.7% by weight or more, or 0.8% by weight or more In another example, the magnesium oxide content is 5% by weight or less, for example 4. 5% by weight or less, 4% by weight or less, 3.5% by weight or less, 3% by weight or less, or 2.8% by weight or less The magnesium oxide content may be less than or equal to any of the above minimum percentages. It will be appreciated that the range can be inclusive of any percentage of the maximum. For example, the content is within a range of 0.1% by weight to 5% by weight, 0.3% by weight to 4.5% by weight, It may be in the range of 0.7% to 2.8% by weight. In one embodiment, the nanocrystalline alumina is alumina having a minimum of 0.1 to 0.25% by weight of the nanocrystalline alumina. and magnesium oxide within a range between any one of and any one of the maximum values, The content of magnesium oxide relative to the total weight of the abrasive article is preferably within the range described herein. It will also be understood that the present invention may include any of the percentages or ranges set forth herein. In another specific embodiment, the abrasive particles are comprised of nanocrystalline alumina and Magnesium oxide within a range between any of the minimum and maximum values disclosed herein; and It may consist essentially of
[0045] In another example, the additive can include zirconium oxide (ZrO2); The nanocrystalline abrasive particles can facilitate the formation and / or improve the performance of the abrasive article. The content of zirconium oxide relative to the total weight of lumina is, for example, 0.1% by weight or more, e.g. 0.3% by weight or more, 0.5% by weight or more, 0.7% by weight or more, 0.8% by weight or more, 1% by weight or more, 1.3% by weight or more, 1.5% by weight or more, 1.7% by weight or more, or 2% by weight or more In another example, the content of zirconium oxide is 8% by weight or less, 7% by weight or less. or less, 6% by weight or less, 5.8% by weight or less, 5.5% by weight or less, or 5.2% by weight or less The zirconium oxide content may range from any of the above minimum percentages to a maximum of It will be understood that the range may include any of the percentages of. The content is preferably within a range of 0.1% by weight to 8% by weight, more preferably within a range of 0.3% by weight to 7% by weight, and even more preferably within a range of 0.1% by weight to 8% by weight, even more preferably within a range of 0.3% by weight to 7% by weight, and even more preferably within a range of 0.3% by weight to 7% by weight. Alternatively, it may be in the range of 0.5% to 5.8% by weight. For example, nanocrystalline alumina is a mixture of alumina and zirconia within the scope of the embodiments herein. The content of zirconium oxide relative to the total weight of the abrasive particles may be essentially the same as that of zirconium oxide. Amounts may include any of the percentages or ranges described herein. It will be appreciated that in another particular embodiment, the abrasive particles may be nanocrystalline. alumina and between any of the minimum and maximum percentages mentioned above and ZrO2 within the range.
[0046] In one embodiment, the additives facilitate the formation and / or improve the performance of the abrasive article. Magnesium oxide (MgO) and zirconium oxide (Z) can be added in a specific ratio. The additive ratio (MgO / ZrO2) is 1:1 zirconium oxide. The weight percentage of magnesium oxide in the case of MgO is 1.0%. The weight percent of MgO in crystalline alumina and ZrO2 in nanocrystalline alumina. For example, this ratio is less than 1.5, e.g., less than 1.4. , 1.3 or less, 1.2 or less, 1.1 or less, 1 or less, 0.95 or less, 0.9 or less, 0.85 or less, 0.8 or less, 0.75 or less, 0.7 or less, 0.65 or less, 0.6 or less, or 0. 55 or less. In another example, the additive ratio (MgO / ZrO2) is about 0.01 or more, 0.05 or more, 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, or The additive ratio (MgO / ZrO2) can be set to 0.5 or more. It will be understood that the range can be inclusive of any ratio up to any maximum ratio. For example, the additive ratio (MgO / ZrO2) is within the range of 0.01 to 1.5, 0.1 to 1. It may be in the range of 1, or in the range of 0.3 to 0.95. In this case, the nanocrystalline alumina is alumina in any of the minimum ratios described herein. Magnesium oxide and zinc oxide in the range of additive ratios from 0.01 to 0.01 to the maximum ratio, inclusive. The abrasive particles may consist essentially of ruthenium and zinc. Contains magnesium oxide (MgO) and zirconium oxide (ZrO2) in weight percent. It will also be appreciated that in certain embodiments, the abrasive particles may be nanocrystalline. Alumina having a ratio of from any of the minimum ratios to any of the maximum ratios described herein. and essentially consisting of magnesium oxide and zirconium oxide in an additive ratio within a range including It is also possible.
[0047] According to one embodiment, the additive may include calcium oxide (CaO). Crystalline alumina can facilitate formation of and / or improve the performance of the abrasive article. It can contain a specific content of calcium oxide relative to the total weight of nanocrystalline alumina. For example, the calcium oxide content is 0.01% by weight or more, for example, 0.05% by weight or more, Approximately 0.07% by weight or more, 0.1% by weight or more, 0.15% by weight or more, 0.2% by weight or more, In another example, the content may be 5% by weight or more. For example, 4% by weight or less, 3% by weight or less, 2% by weight or less, 1% by weight or less, 0.7% by weight or less The calcium oxide content may be less than the above minimum ratio, or less than 0.5% by weight. It is understood that the range can be inclusive of any of the above to any of the maximum ratios. For example, the content is within the range of 0.01% by weight to 5% by weight, 0.07% by weight to 3.5% by weight, % by weight or in the range of 0.15% to 0.7% by weight. In some embodiments, the nanocrystalline alumina is alumina as described herein. A content within a range between any of the minimum percentages and any of the maximum percentages, inclusive and calcium oxide. The calcium content may be any of the percentages or ranges described herein. It will be appreciated that the abrasive grains may include any of the following: The child is a mixture of nanocrystalline alumina and one of the minimum and maximum percentages mentioned above. and ZrO2 within any range therebetween.
[0048] According to another embodiment, the additive is magnesium oxide (MgO) and calcium oxide ( Nanocrystalline alumina has an additive ratio (CaO / MgO). where MgO is the weight percent of MgO in the nanocrystalline alumina; CaO is the weight percent of CaO in the nanocrystalline alumina. The addition ratio is: This can facilitate improved formulation and / or performance. For example, the additive ratio can be less than 1, e.g. For example, 0.95 or less, 0.9 or less, 0.85 or less, 0.8 or less, 0.75 or less, 0.7 or less , 0.65 or less, 0.6 or less, 0.55 or less, 0.5 or less, 0.45 or less, or 0.4 In another example, the ratio may be 0.01 or more, such as 0.05 or more, such as 0.1 The additive ratio ( CaO / MgO) shall be within the range including either the minimum ratio or the maximum ratio mentioned above. For example, the additive ratio may be within the range of 0.01 to 1, 0.0 It may be in the range of 5 to 0.9, or in the range of 0.1 to 0.75. In terms of form, nanocrystalline alumina is a mixture of alumina and the minimum of the nanocrystalline alumina described herein. Magnesium oxide and oxide in a range of additive ratios including any of the ratios and the maximum ratio The calcium oxide for magnesium oxide can essentially consist of calcium oxide. The additive ratios of the ruthenium include any of the ratios or ranges described herein. It will also be appreciated that in another particular embodiment, the abrasive particles may be nanocrystalline. Crystalline alumina and additives in the range between any of the minimum ratios and any of the maximum ratios listed above. The composition may consist essentially of calcium oxide and magnesium oxide in the ratio.
[0049] According to one embodiment, the nanocrystalline alumina may include rare earth oxides. Examples of oxides of this type are yttrium oxide, cerium oxide, praseodymium oxide, and sam Lithium oxide, Ytterbium oxide, Neodymium oxide, Lanthanum oxide, Gadolinium oxide, Dioxide These may include sprosium, erbium oxide, or precursors thereof. In the present embodiment, the rare earth oxide is yttrium oxide, cerium oxide, praseodymium oxide, Samarium oxide, ytterbium oxide, neodymium oxide, lanthanum oxide, gadolinium oxide , dysprosium oxide, erbium oxide, precursors thereof, and combinations thereof. In another embodiment, the nanocrystalline alumina can be selected from the group consisting of rare earth It may be essentially free of oxides and iron. The abrasive particles are magnetoplumbite phase containing rare earths, divalent cations, and alumina. The structure may include any phase. An example of the magnetoplumbite structure is MgLaAl 11 O1 The number is 9.
[0050] According to one embodiment, the nanocrystalline alumina may include rare earth alumina crystallites. According to another embodiment, the nanocrystalline alumina may include a rare earth aluminate phase. Additionally, according to another embodiment, the nanocrystalline alumina may include a spinel material. The abrasive particles may be rare earth alumina crystallites, rare earth aluminate phases, or spinel It will be appreciated that the material may include fluororubber materials.
[0051] According to one embodiment, the nanocrystalline alumina is a nanocrystalline alumina having nanocrystalline particles (e.g., grains or The nanocrystalline particles may include nanocrystalline domains, which may improve the formation and / or performance of the abrasive article. In certain embodiments, each nanocrystalline particle may be a nanocrystalline The total volume of the polymer particles is 50% or more of crystalline material, e.g., monocrystalline material or polycrystalline material. For example, each particle may be made up of 75% or more crystalline material by volume, 85% or more crystalline material by volume, crystalline material, 90% or more by volume crystalline material, or 95% or more by volume crystalline material. In certain embodiments, the nanocrystalline particles can consist essentially of crystalline material. The above-mentioned characteristics of nanocrystalline alumina can be applied to abrasive particles. For example, each abrasive particle may be made of crystalline material that accounts for 50% or more by volume of the total volume of each abrasive particle. The abrasive particles may include, for example, a single crystal material or a polycrystalline material. alumina and one or more additives as described in the embodiments herein. It will be appreciated that the material may consist essentially of crystalline materials, including at least one of In at least one embodiment, the abrasive particles are comprised of alpha alumina and and one or more additives as described in the embodiment. It may also be possible to use the same method.
[0052] In one embodiment, the nanocrystalline alumina has specific properties including Vickers hardness and density. For example, nanocrystalline alumina has a Vickers hardness of 18. GPa or more, 18.5GPa or more, 19GPa or more, or even 19.5GPa or more In another example, the Vickers hardness of nanocrystalline alumina can be 26 .5GPa or less, e.g., 26GPa or less, 25.5GPa or less, 25GPa or less, or Furthermore, it may be 24.5 GPa or less. Nanocrystalline alumina is not limited to any of the above minimum values. 2. The hardness of the Vickers scale can be within a range including any of the values up to the maximum value. For example, the Vickers hardness is in the range of 18GPa to 24.5, or 19 In another embodiment, the nanocrystalline The physical properties of alumina can be applied to abrasive particles in a similar manner. For example, the abrasive particles , and may have the Vickers hardnesses mentioned above.
[0053] The Vickers hardness is measured by the diamond indentation method (the method of the present invention) on the polished surface of the abrasive grain. It will be understood that the measurement is based on the surface roughness of the polished grains (which is well known in the art). After preparing the Bakelite mount in epoxy resin, the Struers Tegramin 3 0 Use the polishing unit to polish with diamond polishing slurry. The Instron-Tukon 2100 Microhardware is used. Using an ESS tester, five different Five diamond indentations are measured with an abrasive particle. The measurements are in Vickers units. Convert the KPa units to GPa by dividing by 100. For optimal sample size purposes, The hardness average and range are reported and statistically relevant calculations are performed.
[0054] In one embodiment, the nanocrystalline alumina can have a non-friable property. The fracture of nanocrystalline alumina compared to that of microcrystalline alumina with the same grain size. Both destructions are measured in the same manner as disclosed in more detail below. The friability of crystalline alumina can be expressed in percent form and the corresponding friability of microcrystalline alumina can be expressed in percent form and the friability of microcrystalline alumina can be expressed in percent form. Lumina friability is taken as the standard and set to 100%. In one embodiment, nanocrystals The friability of the crystalline alumina can be greater than 100%. The friability is 102% or more, for example 105% or more, 108% or more, 110% or more, 112% or more, % or more, 115% or more, 120% or more, 125% or more, or 130% or more. In another example, the nanocrystalline alumina may have a friability of 160% or less. stomach.
[0055] Friability is generally measured using tungsten carbide balls having an average diameter of 3 / 4 inch at a given The particle sample was ground for a period of time, the material from the ball mill was sieved, and the crushing ratio of the reference sample was The percent fracture of the sample is measured by measuring the percent fracture of the sample relative to the percent fracture of the sample. In an embodiment, the reference sample was a microcrystalline alumina sample having the same grain size. Ta.
[0056] Before the ball mill, a reference sample (e.g., Saint-Gobain Corporat (microcrystalline alumina available from Ion as Cerpass® HTB) Approximately 300 to 350 grams of crystal grains were placed on a Ro-Tap (registered trademark) manufactured by WS Tyler Inc. The samples were sieved using a set of screens placed on a sieve shaker (model RX-29) (registered trademark). The screen size is determined by a set number and type of sieve above and below the target particle size. For example, if the target particle size of the coarse grain is 80, In this case, the process uses the following US standard sieve sizes: 1) 60; 2) 70; 3) 80; 4 ) 100; and 5) 120. The screens are arranged so that the coarse grain size is from the top to the bottom. Stack the bottom screen so that it is larger than the bottom screen, and place a tray under the bottom screen to hold all the screens in place. The grains that fall through are collected. The Ro-Tap® sieve shaker is run at 1000rpm every minute. The test was run for 10 minutes at a vibration speed of 287±10 and tap count of 150±10. Only the particles on the screen with a size (hereafter referred to as the target screen) are included in the target particle size sample. The same process is repeated for test samples of other materials to obtain target particle size samples. Collect.
[0057] After sieving, a portion of each of the target particle size samples is subjected to grinding.
[0058] Place a clean, empty mill container into the roller mill. Set the roller speed to 305 rpm. Set the mill bowl speed to 95 rpm. Average diameter 3 / 4 inch flattened spheres Approximately 3500 grams of tungsten carbide balls are placed in the container. Place 100 grams of material into the mill container along with the balls. Close the container and place it in the ball mill. Run the ball mill for 1 to 10 minutes. Stop the ball mill and shake the mixture in a Ro-Tap® sieve. Using a shaker and the same screen used to prepare the target particle size samples, The balls and grains are sieved using the same conditions as above. Run for 5 minutes to obtain a target particle size sample. Collect all particles that fall through the target screen. The percent destruction of the control sample is calculated by dividing the mass of grains that passed through the target screen by the mass of grains that passed through the target screen. is the target particle size divided by the initial mass of the sample (i.e., 100 grams). If the percentage is within the range of 48% to 52%, a second 100 gram sample of the target particle size is The test is carried out under exactly the same conditions as those used for the eye samples to measure reproducibility. If the sample shows a percent destruction between 48% and 52%, record the value. If the percent destruction does not reach 52%, adjust the grinding time or use a different sample. The crushing time is adjusted until the percentage of destruction is within the range of 48% to 52%. This was repeated until two consecutive samples showed percent failure within the range of 48% to 52%. and record these results.
[0059] The percent destruction of a typical sample material (e.g., nanocrystalline alumina particles) ranged from 48% to The test is performed in the same manner as the control sample with 52% destruction. The relative friability of a nanocrystalline sample is the fracture of a nanocrystalline sample compared to the fracture of a reference microcrystalline sample.
[0060] In another example, the nanocrystalline alumina has a molecular weight of 3.85 g / cc or more, for example 3.9 g / cc or more. cc or more, or a density of 3.94 g / cc or more. In the case of nanocrystalline alumina, the density is 4.12 g / cc or less, for example, 4.08 g / cc. It may be 4.02 g / cc or less, or even 4.01 g / cc or less. The crystalline alumina may range from any of the minimum values to any of the maximum values set forth herein. It will be appreciated that the density may be in the range including, for example, 3.8 Within the range of 5g / cc~4.12g / cc or 3.94g / cc~4.01g / cc The density of the abrasive particles can be any of the values described herein, or It will also be understood that any of the ranges may be included.
[0061] According to one embodiment, the abrasive particles may include at least one type of abrasive particle. For example, the abrasive particles may be a blend including a first type of abrasive particles and a second type of abrasive particles. The first type of abrasive particles may include nanoparticles according to any of the embodiments herein. The second type of abrasive particles includes oxides, carbides, nitrides, and zeolites. oxides, borides, oxycarbides, oxynitrides, superabrasives, carbon-based materials, aggregates, conglomerates, At least one selected from the group consisting of shaped abrasive particles, diluent particles, and combinations thereof. In certain embodiments, the abrasive particles are nanocrystalline in nature. It may be made of crystalline alumina.
[0062] In one embodiment, the body of the abrasive article of the embodiments herein comprises a fixed abrasive article. In another embodiment, the body portion can include an abrasive article. The stone article may include abrasive grains contained in a three-dimensional matrix of a binder. The stone body may be formed into any suitable shape known to those skilled in the art. Suitable shapes include: , abrasive wheels, cones, horns, cups, flanged wheels, tapered cups, segments, shank end tools, discs, thin wheels, and large diameter cut-off wheels.
[0063] According to one embodiment, the body of the abrasive article is formed to improve the formation and / or performance of the abrasive article. The abrasive particles may be included in a specific content that can facilitate the abrasive particles. For example, The content is 2% or more, 4% or more, 6% or more, or 8% or more by volume of the total volume of the main body. , 10% by volume or more, 12% by volume or more, 14% by volume or more, 16% by volume or more, 18% by volume or more , 20% by volume or more, 25% by volume or more, 30% by volume or more, or even 35% by volume or more. In another example, the content of the abrasive particles in the grindstone body is 65% by volume. For example, 64% by volume or less, 62% by volume or less, 60% by volume or less, 58% by volume or less, 56 % or less by volume, about 54% or less by volume, 52% or less by volume, 50% or less by volume, 48% or less by volume, 4 6% by volume or less, 44% by volume or less, 42% by volume or less, 40% by volume or less, 38% by volume or less, 3 6% by volume or less, 34% by volume or less, 32% by volume or less, 30% by volume or less, or more than 28% by volume , 26% by volume or less, 24% by volume or less, 22% by volume or less, or 20% by volume or less. The abrasive particle content may be any of the minimum and maximum percentages listed above. It will be understood that the range can include any of the following: The content of the element is within the range of 2% to 64% by volume, 12% to 62% by volume, or can be in the range of 20% by volume to 58% by volume.
[0064] In one embodiment, the content of nanocrystalline alumina relative to the total volume of the body is The nanocrystalline nature of the material may be controlled to facilitate improved formation and / or performance of the article. The alumina content is 1 vol% or more, for example, 2 vol% or more, 4 vol% or more, or 6 vol% or more. , 8 vol% or more, 10 vol% or more, 12 vol% or more, 14 vol% or more, 16 vol% or more, 18% by volume or more, 20% by volume or more, 25% by volume or more, 30% by volume or more, or 35% by volume In another embodiment, the content of nanocrystalline alumina can be 6 5% by volume or less, for example, 64% by volume or less, 62% by volume or less, 60% by volume or less, 58% by volume or less Lower, 56% or less by volume, about 54% or less by volume, 52% or less by volume, 50% or less by volume, 48% by volume Below 46% by volume, below 44% by volume, below 42% by volume, below 40% by volume, below 38% by volume or less, 36% by volume or less, 34% by volume or less, 32% by volume or less, 30% by volume or less, or 28 % by volume, 26% by volume or less, 24% by volume or less, 22% by volume or less, or 20% by volume or less The abrasive particle content may vary from any of the minimum percentages above to the maximum percentages above. It will be understood that the range can include any of the above. The content of nanocrystalline alumina in the range of 2% by volume to 64% by volume, 12% by volume to It may be in the range of 62% by volume, or in the range of 20% to 58% by volume.
[0065] According to one embodiment, the body is made of a material having a specific content of binder, as described herein. For example, the content of the binder with respect to the total volume of the main body may be 1% by volume or more. For example, 2% by volume or more, 5% by volume or more, 10% by volume or more, 20% by volume or more, 30% by volume or more , 35% by volume or more, 40% by volume or more, or 45% by volume or more. In this case, the binder content is 98% by volume or less, for example, 95% by volume or less, 90% by volume or less, 8 5% by volume or less, 80% by volume or less, 75% by volume or less, 70% by volume or less, 65% by volume or less, or less than 60% by volume, 55% by volume, 50% by volume, or less than 45% by volume, 40 pieces % or less by volume, or 35% or less by volume, 30% or less by volume, or 25% or less by volume. The binder content may vary from any of the minimum percentages to any of the maximum percentages listed above. It will be appreciated that the scope of the present invention may include, for example, a connection at the body portion. The material content is within the range of 1% to 98% by volume, within the range of 5% to 85% by volume, or It can be within the range of 20% by volume to 70% by volume.
[0066] The body of the abrasive article can be formed to have a particular porosity. In the case of the present invention, the porosity can be 1% by volume or more of the total volume of the main body. The ratio is 2% by volume or more, 4% by volume or more, 6% by volume or more, 8% by volume or more, 10% by volume or more, 2% by volume or more, 14% by volume or more, 16% by volume or more, 18% by volume or more, 20% by volume or more, 2 5% by volume or more, 30% by volume or more, 40% by volume or more, 45% by volume or more, 50% by volume or more, In another embodiment, the porosity of the body portion may be greater than or equal to 55% by volume. For example, the porosity may be 75% by volume or less, 70% by volume or less, 60% by volume or less, or the like. vol% or less, 55 vol% or less, 50 vol% or less, 45 vol% or less, 40 vol% or less, 35 vol% or less, 30 vol% or less, 25 vol% or less, 20 vol% or less, 15 vol% or less, 10 The porosity of the main body may be 5% or less by volume, 2% or less by volume, or 5% or less by volume. The range shall be inclusive of either the smallest percent or the largest percent of For example, the content of the binder in the main body can be 1% by volume to Within the range of 80% by volume, within the range of 8% by volume to 55% by volume, or within the range of 14% by volume to 30% by volume It can be within a range.
[0067] The pores in the body can be of various configurations. For example, the pores can be closed or open. The pores may be porous or may include closed and open pores. The pores are selected from the group consisting of closed pores, open pores, and combinations thereof. In another embodiment, the majority of the porosity may comprise open porosity. In certain embodiments, all of the porosity can be essentially open porosity. Furthermore, in another embodiment, the majority of the pores may include closed pores. For example, All of the pores may be essentially closed pores.
[0068] The body may include pores having a particular average pore size. In one embodiment, , the average pore size is 500 microns or less, for example 450 microns or less, 400 microns or less , 350 microns or less, 300 microns or less, 250 microns or less, 200 microns or less , 150 microns or less, or 100 microns or less. The average pore size is 0.01 microns or more, 0.1 microns or more, or 1 micron or more. The main body may be any of the minimum values and any of the maximum values mentioned above. It will be appreciated that the average pore size of the body may be in the range of 0.1 to 1.0 mm. Pore size ranges from 0.01 microns to 500 microns, 0.1 microns to 350 microns or in the range of 1 micron to 250 microns.
[0069] According to one embodiment, the abrasive particles of the embodiments herein may include unagglomerated particles. Abrasive particles, such as those comprising nanocrystalline alumina, can be non-agglomerated particles. According to embodiments, the abrasive particles may include agglomerated particles, such as nanocrystalline alumina. The abrasive particles comprising may be agglomerated particles.
[0070] In one embodiment, the abrasive particles comprising nanocrystalline alumina are shaped abrasive particles. The particles can have a two-dimensional shape, a three-dimensional shape, or a combination thereof. Possible 2D shapes include regular polygons, non-regular polygons, irregular shapes, triangles, partially concave triangles, etc. Square, quadrilateral, rectangle, trapezoid, pentagon, hexagon, heptagon, octagon, ellipse, Greek al Alphabet, Latin alphabet, Russian alphabet, and According to one embodiment, the abrasive particles are any of the two-dimensional shapes described above. Exemplary three-dimensional shapes include a polyhedron, a pyramid, an ellipsoid, Sphere, prism, cylinder, cone, tetrahedron, cube, rectangular prism, rhombohedron, truncated pyramid, truncated ellipse Celestial body, truncated sphere, truncated cone, pentahedron, hexahedron, heptahedron, octahedron, nonahedron, decahedron , Greek alphabet letters, Latin alphabet letters, Russian alphabet letters Characters, Chinese characters, complex polygonal shapes, irregular contours, volcano shapes, monostatic shapes, and combinations thereof. A monostatic shape has a single stable rest position. According to another embodiment, the abrasive particles may be in the three-dimensional shape described above. In certain embodiments, the shaped abrasive particles may be triangular. In another particular embodiment, the shaped abrasive particles can have a two-dimensional shape. The shaped abrasive particles and the method of formation may have a two-dimensional shape of a partially concave triangle. US2013 / 0236725A1 by Doruk O. Yener et al., and Dor uk O. Yener et al., US2012 / 0167481. No. 6,399,433, both of which are incorporated herein by reference in their entireties.
[0071] FIG. 2 includes a perspective view of an exemplary shaped abrasive particle 200. The shaped abrasive particle has a three-dimensional shape. The body portion 201 may include a first end surface 202 and a second end surface 203. The body portion 201 may generally include a first end surface 202 and a second end surface 203. The shaped abrasive particles 200 may be rectangular prisms having two end faces 204. The first side 210 may include a first end surface 202 and a second end surface 204. The second side 212 is adjacent to the first side 210 and is connected to the first end surface 202 and the second end surface 203. As shown, the shaped abrasive particle 200 may extend between the second side 212 and A third end surface 202 extends adjacent to the first side surface 210 and between the first end surface 202 and the second end surface 204. As shown, each end surface 202 of the shaped abrasive particle body portion 201 may also include a side surface 214. 204 may be generally triangular in shape. Each side 210, 212, 214 may be generally Further, the shaped abrasive particles in a plane parallel to the end faces 202, 204 may be rectangular in shape. The cross section of the body portion 201 is generally triangular.
[0072] 3 includes a perspective view of another abrasive particle 300. As shown, the abrasive particle 300 has an upper surface 3 The three-dimensional shape includes a main body portion 301 having a top surface 305 and a bottom surface 306 opposite the top surface 305. As further shown, the body portion 301 may have a top surface 305 and a bottom surface 306. The casing 302 may be formed having sides 302, 303, 307, and 308 extending do.
[0073] As shown, the body portion 301 has a body length (Lb), a body width (Wb), and a body The thickness (Tb) of the portion may be such that Lb>Wb, Lb>Tb, and Wb>Tb. In certain embodiments, the body has a first aspect ratio (Lb:Wb) of 1:1 or greater. For example, the aspect ratio (Lb:Wb) can be 2:1. The ratio may be greater than 1:1, greater than 3:1, greater than 5:1, or greater than 10:1. For this, the aspect ratio (Lb:Wb) must be 1000:1 or less, or 500:1 or less. The aspect ratio (Lb:Wb) can be any of the minimum values to any of the maximum values listed above. It will be understood that the ratio can be within a range including, for example, 1:1 to 1000:1. According to another embodiment, the body has a ratio of 1:1 or more, 2:1 or more, 3:1 or more, 5:1 or more. or a second aspect ratio (Lb:Tb) of 10:1 or greater. The second aspect ratio (Lb:Tb) may be about 1000:1 or less. ) is within a range including any of the minimum values to any of the maximum values mentioned above, for example, 1:1 to It will be appreciated that the ratio may be as high as 1000:1. The main body is a 1:1 or more, 2:1 or more, 3:1 or more, 5:1 or more, or 10:1 or more The third aspect ratio (Wb:Tb) can be about 10 The third aspect ratio (Wb:Tb) may be any of the minimum values described above. The range can be from one to the maximum, for example, 1:1 to 1000:1. It will be understood that it is possible.
[0074] In a further embodiment, the length (Lb) of the body portion, the width (Wb) of the body portion, and the At least one of the thicknesses (Tb) of the portions has an average dimension of 0.1 microns or more. For example, the average size can be 1 micron or more, 10 microns or more, or 50 microns or more. , 100 microns or more, or 150 microns or more, 200 microns or more, 400 microns It can be 100 microns or more, 600 microns or more, 800 microns or more, or 1 mm or more. In another example, the average dimension is 20 mm or less, e.g., 18 mm or less, 16 mm or less, 14 mm or less. mm or less, 12 mm or less, 10 mm or less, 8 mm or less, 6 mm or less, or 4 mm or less The average size may range from any of the minimum values to any of the maximum values mentioned above, inclusive. For example, 1 micron to 20 mm, 10 microns to 18 mm, 50 microns to 14 mm, Alternatively, it will be understood that it can be between 200 microns and 8 mm.
[0075] According to one embodiment, the body portion is disposed in a plane defined by a length of the body portion and a width of the body portion. The cross-sectional shape may be a triangle, a quadrilateral, a rectangle, or the like. , trapezoid, pentagon, hexagon, heptagon, octagon, ellipse, Greek alphabet letters, latte may include Japanese alphabet characters, Russian alphabet characters, and combinations thereof. According to another embodiment, the body is defined by a body length and a body thickness. The cross-sectional shape may be a triangle, a rectangle, Rectangles, trapezoids, pentagons, hexagons, heptagons, octagons, ellipses, Greek alphabet letters , Latin alphabet characters, Russian alphabet characters, and combinations thereof. The body portion may have any of the cross-sectional shapes described above. 4 is generally quadrilateral in shape when viewed in a plane defined by its width and thickness, and more particularly FIG. 5 includes a cross-sectional view of an abrasive particle 400 having a rectangular two-dimensional shape. When viewed in a plane defined by the length and width, the two-dimensional shape may be generally octagonal. 5 includes a perspective view of an abrasive particle 500 that can be used.
[0076] Many different aspects and embodiments are possible. Some of these aspects and embodiments are After reading this specification, those skilled in the art will understand these aspects and It should be appreciated that the embodiments and examples are merely illustrative and are not intended to limit the scope of the present invention. Moreover, those skilled in the art will appreciate that some embodiments that include analog circuitry may be implemented using digital circuitry. It will be appreciated that this can be implemented similarly using and vice versa. The embodiment may be according to any one or more of the following embodiments.
[0077] Embodiment 1. A binder comprising an inorganic material, including a ceramic; and Abrasive particles contained in a binder, the abrasive particles comprising nanocrystalline alumina Main body including 1. An abrasive article comprising:
[0078] Embodiment 2. A binder comprising an inorganic material, including a ceramic; and Abrasive particles contained in a binder, the abrasive particles comprising nanocrystalline alumina forming a mixture comprising: by heating the mixture to a forming temperature of about 900° C. or more and about 1200° C. or less; Forming the mixture into an abrasive article A method of forming an abrasive article comprising:
[0079] Embodiment 3. The method of embodiment 1 or 2, wherein the bonding material comprises a glass material having an amorphous phase. The abrasive article or method of
[0080] Embodiment 4. The method of embodiment 1 or 2, wherein the bonding material comprises a non-glass material having a polycrystalline phase. The abrasive article or method as described.
[0081] Embodiment 5. The method of embodiment 1 or 2, wherein the binder comprises a mixture of a polycrystalline material and a glass material. The abrasive article or method described in claim 1.
[0082] Embodiment 6. The method of embodiment 1 or 2, wherein the bonding material consists essentially of a glass material having an amorphous phase. 2. The abrasive article or method according to claim 1.
[0083]
[0036] Embodiment 7. The binder is about 30% by weight or less, or about 28% by weight or less, of the total weight of the binder. or about 26% by weight or less, or about 24% by weight or less, or about 22% by weight or less of phosphatase 3. The abrasive article or method of embodiment 1 or 2, comprising uranyl (B2O3).
[0084] Embodiment 8. The binder comprises at least about 5% by weight, or at least about 8% by weight, or or about 10% by weight or more, or about 12% by weight or more, or about 15% by weight or more of boron oxide 3. The abrasive article or method of embodiment 1 or 2, comprising (B2O3).
[0085] Embodiment 9. The binder is about 80% by weight or less, or about 75% by weight or less, of the total weight of the binder. or about 70% by weight or less, or about 65% by weight or less, or about 60% by weight or less, or About 55% by weight or less, or about 52% by weight or less, or about 50% by weight or less of silicon oxide (S iO2).
[0086] Embodiment 10. The binder comprises about 25% by weight or more, or about 35% by weight or more of the total weight of the binder. or more than about 38% by weight, or more than about 40% by weight of silicon oxide (SiO2) 3. The abrasive article or method of embodiment 1 or 2.
[0087] Embodiment 11. The binder comprises boron oxide (B2O3) and silicon oxide (SiO2). The total content of boron oxide and silicon oxide is about 80% by weight or less, or about 77% by weight or less. or less than about 75% by weight, or less than about 73% by weight, or less than about 70% by weight, 3. The polishing composition of claim 1 or 2, wherein the amount of the at least one carboxylic acid is about 70% by weight or less, or about 65% by weight or less. An item or method.
[0088] Embodiment 12. The binder comprises boron oxide (B2O3) and silicon oxide (SiO2). The total content of boron oxide and silicon oxide is about 40% by weight or more, or about 42% by weight or more. or about 46% by weight or more, or about 48% by weight or more, or about 50% by weight or more; 3. The abrasive article or method of embodiment 1 or 2.
[0089] Embodiment 13. The binder has a ratio of about 5.5:1 or less, or about 5.2:1 or less, or about 5: Weight percent of silicon oxide (SiO2) less than or equal to 1, or less than or equal to 4.8:1:boron oxide (B2O3) by weight percent ratio. is the method.
[0090]
[0036] Embodiment 14. The binder is a cellulose acetate copolymer having a molecular weight of about 1:1 or more, or about 1.3:1 or more, or about 1.5: 1 or greater, or greater than about 1.7:1, or greater than about 2.0:1, or greater than about 2.2:1 The ratio of weight percent of silicon (SiO2) to weight percent of boron oxide (B2O3) is 3. The abrasive article or method of embodiment 1 or 2, comprising:
[0091] Embodiment 15. The binder is about 5% by weight or more, or about 8% by weight or more, based on the total weight of the binder; or about 10% by weight or more, or about 12% by weight or more, or about 14% by weight or more of aluminum oxide; 3. The abrasive article or method of embodiment 1 or 2, comprising aluminium (Al2O3).
[0092] Embodiment 16. The binder is about 30% by weight or less, or about 28% by weight or less, based on the total weight of the binder. or less than about 25% by weight, or less than about 23% by weight, or less than about 20% by weight 3. The abrasive article or method of embodiment 1 or 2, comprising aluminum (Al2O3).
[0093] Embodiment 17. The binder is a mixture of aluminum oxide (Al2O3) and silicon oxide (SiO2 ), the total content of aluminum oxide and silicon oxide being about 50% by weight or more; or About 52% by weight or more, or about 56% by weight or more, or about 58% by weight or more, or about 60% by weight or more 3. The abrasive article or method of embodiment 1 or 2, wherein the abrasive particle size is 0.05 to 0.1 mm.
[0094] Embodiment 18. The binder is a mixture of aluminum oxide (Al2O3) and silicon oxide (SiO2 ), with a total content of aluminum oxide and silicon oxide of about 80% by weight or less; or In embodiments, the weight percent is about 77% or less, or about 75% or less, or about 73% or less. 3. The abrasive article or method according to claim 1 or 2.
[0095] Embodiment 19. The binder has a ratio of about 2.5:1 or less, or about 2.2:1 or less, or about 2: Weight percent of silicon oxide (SiO2) less than 1: weight percent of aluminum oxide (Al2O3) 3. The abrasive article or method of embodiment 1 or 2, having a ratio of weight percent.
[0096]
[0031] Embodiment 20. The binder is a cellulose acetate copolymer having a cellulose acetate ratio of about 1:1 or more, or about 1.3:1 or more, or about 1.5: The weight percent of silicon oxide (SiO2) to aluminum oxide is greater than or equal to 1, or greater than about 1.7:1. 3. The composition of claim 1 or 2 having a weight percent ratio of 0.1 to 0.1% by weight of aluminum (Al2O3). Abrasive article or method.
[0097] Embodiment 21. The binder comprises at least one alkaline earth oxide compound (RO). The total content of alkaline earth oxide compounds (RO) is about 3.0% by weight of the total weight of the binder. or less than about 2.5% by weight, or less than about 2% by weight. The abrasive article or method as described.
[0098] Embodiment 22. The binder comprises at least one alkaline earth oxide compound (RO). , the total content of alkaline earth oxide compounds (RO) is about 0.5% by weight or more, or 0. 8% by weight or greater.
[0099] Embodiment 23. The binder is selected from calcium oxide (CaO), magnesium oxide (MgO), About three or more selected from the group consisting of barium oxide (BaO), strontium oxide (SrO), 3. The polishing method according to claim 1 or 2, comprising the following different alkaline earth oxide compounds (RO): An item or method.
[0100]
[0036] Embodiment 24. The binder comprises at least about 0.5 wt. % of the total weight of the binder, or at least about 0.8 wt. % or more, or about 1% or more by weight of calcium oxide (CaO). The abrasive article or method described in claim 1.
[0101] Embodiment 25. The binder comprises about 3 wt.% or less, or about 2.8 wt.% or less, based on the total weight of the binder. or less than about 2.5%, or less than about 2%, or less than about 1.7% by weight of acid 3. The abrasive article or method of embodiment 1 or 2, comprising calcium oxide (CaO).
[0102] Embodiment 26. The binder is selected from the group consisting of lithium oxide (Li2O), sodium oxide (Na2O), From potassium oxide (K2O) and cesium oxide (Cs2O) and their combinations The compound according to embodiment 1 or 2. The abrasive article or method of claim 1.
[0103] Embodiment 27. The binder comprises at least one alkali oxide compound (RO); The total content of alkali oxide compounds (RO) is about 25% by weight or less, or about 22% by weight or less. 3. The abrasive article or method of embodiment 1 or 2, wherein the abrasive content is less than or equal to about 20% by weight. .
[0104] Embodiment 28. The binder comprises at least one alkali oxide compound (RO); The total content of alkali oxide compounds (RO) is about 3% by weight or more, or about 5% by weight or more % by weight or more, or about 7% by weight or more, or about 9% by weight or more. Abrasive article or method.
[0105] Embodiment 29. The binder comprises about 1 wt.% or more, or about 1.5 wt.% or more, based on the total weight of the binder. or the composition according to embodiment 1 or 2, which contains about 2% by weight or more of lithium oxide (Li2O). The abrasive article or method described above.
[0106] Embodiment 30. The binder comprises about 7 wt.% or less, or about 6.5 wt.% or less, based on the total weight of the binder. or less than about 6% by weight, or less than about 5.5% by weight, or less than about 5% by weight. 3. The abrasive article or method of embodiment 1 or 2, further comprising lithium (LiO).
[0107] Embodiment 31. The binder comprises at least about 3% by weight, or at least about 4% by weight, of the total weight of the binder; or about 5% by weight or more of sodium oxide (Na2O), The abrasive article or method of
[0108] Embodiment 32. The binder comprises about 14% by weight or less, or about 13% by weight or less, based on the total weight of the binder. or less than about 12% by weight, or less than about 11% by weight, or less than about 10% by weight 3. The abrasive article or method of embodiment 1 or 2, comprising sodium (Na2O).
[0109] Embodiment 33. The binder comprises about 1 wt.% or more, or about 1.5 wt.% or more, based on the total weight of the binder. or as described in embodiment 1 or 2, which contains about 2% by weight or more of potassium oxide (K2O). The abrasive article or method of
[0110] Embodiment 34. The binder comprises about 7 wt.% or more, or about 6.5 wt.% or more, based on the total weight of the binder. or less than about 6% by weight, or less than about 5.5% by weight, or less than about 5% by weight. 3. The abrasive article or method of embodiment 1 or 2, further comprising sodium (KO).
[0111] Embodiment 35. The binder comprises about 3.0% by weight or less of phosphorus oxide (P2O5); 3. The polishing method of claim 1 or 2, wherein the bond is essentially free of phosphorus oxide (P2O5). An item or method.
[0112] Embodiment 36. The binder is selected from the group consisting of TiO2, Fe2O3, MnO2, ZrSiO2, and CoAl The composition is essentially free of oxide compounds selected from the group consisting of MgO, MgO, and MgO. 3. The abrasive article or method of embodiment 1 or 2, comprising:
[0113] Embodiment 37. The binder is heat treated at about 1200° C. or less, or about 1175° C. or less, or about 11 50° C. or less, or about 1125° C. or less, or about 1100° C. or less. The abrasive article or method of embodiment 1 or 2.
[0114] Embodiment 38. The binder is heat-resistant to about 900° C. or more, or about 950° C. or more, or about 975° C. 3. The abrasive article or method of embodiment 1 or 2, having a forming temperature equal to or greater than 100° C.
[0115] Embodiment 39. The abrasive particles are about 0.15 microns or less, or about 0.14 microns or less. , or about 0.13 microns or less, or 0.12 or less, or 0.11 or less, or 0 3. The method of claim 1 or 2, further comprising the step of: The abrasive article or method as described.
[0116] Embodiment 40. The abrasive particles are about 0.01 microns or greater, or about 0.02 microns or greater. , or about 0.05 microns or more, or about 0.06 microns or more, or about 0.07 microns or more Average crystal size of about 0.08 microns or more, or about 0.09 microns or more 3. The abrasive article of claim 1 or 2, comprising nanocrystalline alumina having a nanosized grain size. is the method.
[0117] Embodiment 41. The nanocrystalline alumina is about 51% by weight or more of the total weight of the particles, or about 6 0% by weight or more, or about 70% by weight or more, or about 80% by weight or more, or about 85% by weight or about 90% by weight or more, or about 92% by weight or more, or about 93% by weight or more, 3. The abrasive article or method of embodiment 1 or 2, comprising about 94% or more by weight alumina. Law.
[0118] Embodiment 42. The nanocrystalline alumina is about 99.9 wt.% or less of the total weight of the particles; or About 99% by weight or less, or about 98.5% by weight or less, or about 98% by weight or less, or about 9 7.5% by weight or less, or about 97% by weight or less, or about 96.5% by weight or less, or about 9 3. The abrasive article or method of embodiment 1 or 2, comprising up to 6 wt. % alumina.
[0119] Embodiment 43. The nanocrystalline alumina is a composite material containing transition metal elements, rare earth elements, alkali metal elements, At least one element selected from the group consisting of an alkaline earth metal element, silicon, and combinations thereof. 3. The abrasive article or method of embodiment 1 or 2, further comprising one additive.
[0120] Embodiment 44. The additive is magnesium, zirconium, calcium, silicon, iron, iridium. a material selected from the group consisting of tritium, lanthanum, cerium, and combinations thereof; 44. The abrasive article or method of embodiment 43, comprising:
[0121] Embodiment 45. The additive is magnesium, zirconium, calcium, silicon, iron, iridium. comprising two or more materials selected from the group consisting of tritium, lanthanum, and cerium; 44. The abrasive article or method of embodiment 43.
[0122] Embodiment 46. The nanocrystalline alumina comprises about 12 weight percent of the total weight of the nanocrystalline alumina particles. percent or less, or about 11% by weight or less, or about 10% by weight or less, or about 9.5% by weight or less % by weight or less, or about 9% by weight or less, or about 8.5% by weight or less, or about 8% by weight or less; or about 7.5% by weight or less, or about 7% by weight or less, or about 6.5% by weight or less, or About 6% by weight or less, or about 5.8% by weight or less, or about 5.5% by weight or less, or about 5. As described in embodiment 43, comprising additives in a total content of 3% by weight or less, or about 5% by weight or less. The abrasive article or method of
[0123] Embodiment 47. The nanocrystalline alumina is about 0.1 parts by weight of the total weight of the nanocrystalline alumina particles. % by weight or more, or about 0.3% by weight or more, or about 0.5% by weight or more, or about 0.7% by weight or more % or more, or about 1% by weight or more, or about 1.3% by weight or more, or about 1.5% by weight or more or about 1.7% by weight or more, or about 2% by weight or more, or about 2.3% by weight or more, or about 2.5% by weight or more, or about 2.7% by weight or more, or about 3% by weight or more in total content. 44. The abrasive article or method of embodiment 43, comprising an additive.
[0124] Embodiment 48. The composition of embodiment 43, wherein the additive comprises magnesium oxide (MgO). Abrasive article or method.
[0125] Embodiment 49. The nanocrystalline alumina is about 0.1 wt.% of the total weight of the nanocrystalline alumina. or more, or about 0.3% by weight or more, or about 0.5% by weight or more, or about 0.7% by weight or more 49. The abrasive article or method of embodiment 48, comprising about 0.8 wt. % or more MgO. Law.
[0126] Embodiment 50. The nanocrystalline alumina is about 5 weight percent or less of the total weight of the nanocrystalline alumina. or about 4.5% by weight or less, or about 4% by weight or less, or about 3.5% by weight or less, 49. The composition of claim 48, comprising about 3 wt. % or less, or about 2.8 wt. % or less, MgO. Abrasive article or method.
[0127] Embodiment 51. The method of embodiment 43, wherein the additive comprises zirconium oxide (ZrO2). Abrasive Article or Method.
[0128] Embodiment 52. The nanocrystalline alumina is about 0.1 wt.% of the total weight of the nanocrystalline alumina. or more, or about 0.3% by weight or more, or about 0.5% by weight or more, or about 0.7% by weight or more or about 0.8% by weight or more, or about 1% by weight or more, or about 1.3% by weight or more, or about 1.5 wt. % or more, or about 1.7 wt. % or more, or about 2 wt. % or more ZrO2 52. The abrasive article or method of embodiment 51, comprising:
[0129] Embodiment 53. The nanocrystalline alumina is about 8% by weight or less of the total weight of the nanocrystalline alumina. , or about 7% by weight or less, or about 6% by weight or less, or about 5.8% by weight or less, or about 52. The method of claim 51, comprising: Abrasive Article or Method.
[0130] Embodiment 54. The additive is magnesium oxide (MgO) and zirconium oxide (ZrO 44. The abrasive article or method of embodiment 43, comprising:
[0131] Embodiment 55. The nanocrystalline alumina has an additive ratio (MgO / ZrO2) of 1.5 or less. where MgO is the weight percent of MgO in the nanocrystalline alumina and ZrO2 is The weight percentage of ZrO2 in nanocrystalline alumina and the additive ratio (MgO / Zr O2) is about 1.4 or less, or about 1.3 or less, or about 1.2 or less, or about 1.1 or less or about 1 or less, or about 0.95 or less, or about 0.9 or less, or about 0.85 or less , or about 0.8 or less, or about 0.75 or less, or about 0.7 or less, or about 0.65 55 or less, or about 0.6 or less, or about 0.55 or less. Product or method.
[0132] Embodiment 56. The nanocrystalline alumina has an additive ratio (MgO / ZrO2 of about 0.01 or more. ), MgO is the weight percent of MgO in the nanocrystalline alumina, and ZrO 2 is the weight percent of ZrO2 in the nanocrystalline alumina, and the additive ratio (MgO / ZrO2) is about 0.05 or more, or about 0.1 or more, or about 0.2 or more, or about 0. 55. The abrasive article of embodiment 54, wherein the abrasive particle size is 3 or more, or about 0.4 or more, or about 0.5 or more. Product or method.
[0133] Embodiment 57. The polishing method of embodiment 43, wherein the additive comprises calcium oxide (CaO). An item or method.
[0134] Embodiment 58. The nanocrystalline alumina comprises about 0.01 weight percent of the total weight of the nanocrystalline alumina. % or more, or about 0.05% by weight or more, or about 0.07% by weight or more, or about 0.1% by weight or more % by weight or more, or about 0.15% by weight or more, or about 0.2% by weight or more, or about 0.25 58. The abrasive article or method of embodiment 57, comprising at least 10% by weight CaO.
[0135] Embodiment 59. The nanocrystalline alumina is about 5% by weight or less of the total weight of the nanocrystalline alumina. , or about 4% by weight or less, or about 3% by weight or less, or about 2% by weight or less, or about 1% by weight or less % or less, or about 0.7% or less, or about 0.5% or less by weight of CaO. 58. The abrasive article or method of embodiment 57.
[0136] Embodiment 60. The additive is magnesium oxide (MgO) and calcium oxide (CaO). 44. The abrasive article or method of embodiment 43, comprising:
[0137] Embodiment 61. The nanocrystalline alumina has an additive ratio (CaO / MgO) of 1 or less; MgO is the weight percent of MgO in nanocrystalline alumina, and CaO is the nanocrystalline The weight percentage of CaO in crystalline alumina, and the additive ratio (CaO / MgO) is approximately 0. .95 or less, or about 0.9 or less, or about 0.85 or less, or about 0.8 or less, or about 0.75 or less, or about 0.7 or less, or about 0.65 or less, or about 0.6 or less, or about 0.55 or less, or about 0.5 or less, or about 0.45 or less, or about 0.4 or less 61. The abrasive article or method of embodiment 60, wherein
[0138] Embodiment 62. The nanocrystalline alumina has an additive ratio (CaO / MgO) of about 0.01 or more. where MgO is the weight percent of MgO in the nanocrystalline alumina and CaO is The weight percentage of CaO in nanocrystalline alumina and the additive ratio (CaO / MgO ) is about 0.05 or more, or about 0.1 or more, or about 0.15 or more, or about 0.2 or more 61. The abrasive article or method of embodiment 60, wherein the abrasive grain size is about 0.5 or greater.
[0139] Embodiment 63. The nanocrystalline alumina is preferably selected from the group consisting of yttrium oxide, cerium oxide, prase oxide, and the like. Odimium oxide, Samarium oxide, Ytterbium oxide, Neodymium oxide, Lanthanum oxide, Gadium oxide Rhenium oxide, dysprosium oxide, erbium oxide, precursors thereof, and combinations thereof 3. The abrasive article or abrasive of embodiment 1 or 2, comprising a rare earth oxide selected from the group consisting of: Or methods.
[0140] Embodiment 64. The method of embodiment 1 or 2, wherein the nanocrystalline alumina comprises rare earth alumina crystallites. 2. The abrasive article or method according to claim 1.
[0141] Embodiment 65. The method of embodiment 1 or 2, wherein the nanocrystalline alumina comprises a spinel material. The abrasive article or method described above.
[0142] Embodiment 66. The nanocrystalline material comprises nanocrystalline particles, each particle being 0.01 to 0.01% by volume of the total volume of each particle. At least about 50% by volume crystalline or polycrystalline material, or at least about 75% by volume crystalline a material or polycrystalline material, or a material or polycrystalline material that is about 85% or more by volume crystalline or polycrystalline; or about 90% by volume or more of crystalline or polycrystalline material, or about 95% by volume or more or each particle comprises a crystalline or polycrystalline material of 3. The abrasive article or method of embodiment 1 or 2, consisting essentially of the material.
[0143] Embodiment 67. The nanocrystalline alumina is essentially free of rare earth oxides and iron. 3. The abrasive article or method of claim 1 or 2.
[0144] Embodiment 68. The method of embodiment 1 or 2, wherein the nanocrystalline alumina comprises a rare earth aluminate phase. 2. The abrasive article or method of claim 1.
[0145] Embodiment 69. The nanocrystalline alumina has a thermal expansion coefficient of about 18 GPa or more, or about 18.5 GPa or more. or above, or 19 GPa or above, or about 19.5 GPa or above, The abrasive article or method of embodiment 1 or 2.
[0146]
[0046] Embodiment 70. The nanocrystalline alumina has a particle size of about 3.85 g / cc or more, or about 3.9 g / cc or more. 3. The composition of claim 1 or 2, having a density of about 3.94 g / cc or more, or about 3.94 g / cc or more. Abrasive Article or Method.
[0147] Embodiment 71. The abrasive article or method of embodiment 1 or 2, wherein the body comprises a fixed abrasive article. Or methods.
[0148] Embodiment 72. The body comprises abrasive grains contained in a three-dimensional matrix of binder. 3. The abrasive article or method of embodiment 1 or 2, comprising an abrasive article.
[0149] Embodiment 73. The body portion comprises at least about 1% by volume, or at least about 2% by volume, of the total volume of the body portion; or about 4% by volume or more, or about 6% by volume or more, or about 8% by volume or more, or about 10 % by volume or more, or about 12% by volume or more, or about 14% by volume or more, or about 16% by volume or more , about 18% by volume or more, or about 20% by volume or more, or about 25% by volume or more, or about 30% by volume or more % or more, or about 35% or more, by volume, of abrasive particles, according to embodiment 1 or 2. Abrasive article or method.
[0150] Embodiment 74. The body portion comprises about 65% by volume or less of the total volume of the body portion. or less than about 62% by volume, or less than about 60% by volume, or less than about 58% by volume, is about 56% by volume or less, or about 54% by volume or less, or about 52% by volume or less, or about 50% by volume or less % or less by volume, or about 48% or less by volume, or about 46% or less by volume, or about 44% or less by volume or less than about 42% by volume, or less than about 40% by volume, or less than about 38% by volume, is about 36% by volume or less, or about 34% by volume or less, or about 32% by volume or less, or about 30% by volume or less % or less by volume, or about 28% or less by volume, or about 26% or less by volume, or about 24% or less by volume % or less, or about 22% or less, or about 20% or less by volume of abrasive particles. 3. The abrasive article or method according to claim 2.
[0151] Embodiment 75. The body portion comprises about 1% by volume or more, or about 2% by volume or more of the total volume of the body portion; or about 4% by volume or more, or about 6% by volume or more, or about 8% by volume or more, or about 10 % by volume or more, or about 12% by volume or more, or about 14% by volume or more, or about 16% by volume or more , about 18% by volume or more, or about 20% by volume or more, or about 25% by volume or more, or about 30% by volume or more % or more, or about 35% or more, by volume, of nanocrystalline alumina, according to embodiment 1 or 2. The abrasive article or method described in claim 1.
[0152]
[0023] Embodiment 76. The body portion comprises about 65% by volume or less, or about 64% by volume or less of the total volume of the body portion. or less than about 62% by volume, or less than about 60% by volume, or less than about 58% by volume, is about 56% by volume or less, or about 54% by volume or less, or about 52% by volume or less, or about 50% by volume or less % or less by volume, or about 48% or less by volume, or about 46% or less by volume, or about 44% or less by volume or less than about 42% by volume, or less than about 40% by volume, or less than about 38% by volume, is about 36% by volume or less, or about 34% by volume or less, or about 32% by volume or less, or about 30% by volume or less % or less by volume, or about 28% or less by volume, or about 26% or less by volume, or about 24% or less by volume or less than about 22 volume percent, or less than about 20 volume percent nanocrystalline alumina. The abrasive article or method of embodiment 1 or 2.
[0153] Embodiment 77. The abrasive particles include a first type of abrasive particles comprising nanocrystalline alumina and an oxide. Materials, carbides, nitrides, borides, oxycarbides, oxynitrides, superabrasives, carbon-based materials, agglomerates A second type selected from the group consisting of agglomerates, aggregates, shaped abrasive particles, and combinations thereof. and a blend comprising: .
[0154] Embodiment 78. The method of embodiment 1 or 2, wherein the abrasive particles consist essentially of nanocrystalline alumina. 2. The abrasive article or method of claim 1.
[0155] Embodiment 79. The body portion comprises at least about 1% by volume, or at least about 2% by volume of the total volume of the body portion; or about 5% by volume or more, or about 10% by volume or more, or about 20% by volume or more, or about 3 0% by volume or more, or about 35% by volume or more, or about 40% by volume or more, or about 45% by volume 3. The abrasive article or method of embodiment 1 or 2, comprising the above bond.
[0156]
[0036] Embodiment 80. The body portion comprises about 98% by volume or less of the total volume of the body portion. or less than about 90% by volume, or less than about 85% by volume, or less than about 80% by volume, is about 75% by volume or less, or about 70% by volume or less, or about 65% by volume or less, or about 60% by volume or less % or less by volume, or about 55% or less by volume, or about 50% or less by volume, or about 45% or less by volume or less than about 40% by volume, or less than about 35% by volume, or less than about 30% by volume, 3. The abrasive article or method of embodiment 1 or 2, comprising about 25% by volume or less of a bond material.
[0157] Embodiment 81. The body portion comprises at least about 1% by volume, or at least about 2% by volume, of the total volume of the body portion; or about 4% by volume or more, or about 6% by volume or more, or about 8% by volume or more, or about 10 % by volume or more, or about 12% by volume or more, or about 14% by volume or more, or about 16% by volume or more or about 18% by volume or more, or about 20% by volume or more, or about 25% by volume or more, or About 30% by volume or more, or about 40% by volume or more, or about 45% by volume or more, or about 50 % or more, or about 55% or more by volume of the polishing material according to embodiment 1 or 2. An item or method.
[0158] Embodiment 82. The body portion comprises about 80% by volume or less of the total volume of the body portion, or about 75% by volume or less of the total volume of the body portion. or less than about 70% by volume, or less than about 60% by volume, or less than about 55% by volume, is about 50% by volume or less, or about 45% by volume or less, or about 40% by volume or less, or about 35% by volume or less % or less by volume, or about 30% or less by volume, or about 25% or less by volume, or about 20% or less by volume or less than about 15% by volume, or less than about 10% by volume, or less than about 5% by volume, or 3. The abrasive article or method of embodiment 1 or 2, having a porosity of about 2% by volume or less.
[0159] Embodiment 83. The body portion is selected from the group consisting of closed pores, open pores, and combinations thereof. 3. The abrasive article or method of embodiment 1 or 2, comprising pores of the type described above.
[0160] Embodiment 84. The body includes pores, the majority of the pores being open pores or essentially all of the pores being open pores. 3. The abrasive article or method of embodiment 1 or 2, wherein the porosity is open porosity.
[0161] Embodiment 85. The body includes pores, a majority of the pores are closed pores, and essentially all of the pores are closed pores. 3. The abrasive article or method of embodiment 1 or 2, wherein the pores are closed pores.
[0162] Embodiment 86. The body is about 500 microns or less, or about 450 microns or less, or is about 400 microns or less, or about 350 microns or less, or about 300 microns or less; Or 250 microns or less, or about 200 microns or less, or about 150 microns or less or pores having an average pore size of about 100 microns or less. The abrasive article or method as described.
[0163] Embodiment 87. The body has a thickness of about 0.01 microns or more, or about 0.1 microns or more, or 3. The composition of claim 1 or 2, comprising pores having an average pore size of about 1 micron or more. Abrasive article or method.
[0164] Embodiment 88. The abrasive particles of embodiment 1, wherein the abrasive particles include nanocrystalline alumina, are non-agglomerated particles. 3. The abrasive article or method according to claim 2.
[0165] Embodiment 89. The abrasive particles of embodiment 1 or 2, wherein the abrasive particles include nanocrystalline alumina are agglomerated particles. 3. The abrasive article or method according to claim 2.
[0166] Embodiment 90. The abrasive particles of embodiment 1, wherein the abrasive particles comprising nanocrystalline alumina are shaped abrasive particles. 3. The abrasive article or method according to claim 2.
[0167] Embodiment 91. The shaped abrasive particles are in the shape of a regular polygon, a non-regular polygon, an irregular shape, a triangle, a segmented shape, or a hexagonal shape. Concave triangles, quadrilaterals, rectangles, trapezoids, pentagons, hexagons, heptagons, octagons, ellipses, and Sha alphabet letters, Latin alphabet letters, Russian alphabet letters 91. The method of claim 90, having a two-dimensional shape selected from the group consisting of: The abrasive article or method described above.
[0168] Embodiment 92. The shaped abrasive particles are in the shape of a polyhedron, pyramid, ellipsoid, sphere, prism, cylinder, circle, or sphere. Pyramid, tetrahedron, cube, rectangular prism, rhombohedron, truncated pyramid, truncated ellipsoid, truncated sphere, truncated cone, pentahedron, hexahedron, heptahedron, octahedron, nonahedron, decahedron, Greek alpha Alphabet characters, Latin alphabet characters, Russian alphabet characters, Chinese characters, composite characters Polygonal shapes, irregular contours, volcano shapes, monostatic shapes, and combinations thereof and a monostatic shape is a single stable stationary shape selected from the group consisting of: 91. The abrasive article or method of embodiment 90, wherein the abrasive article or method is a shape having a position.
[0169] Embodiment 93. The shaped abrasive particles of embodiment 90, wherein the shaped abrasive particles have a triangular two-dimensional shape. Abrasive Article or Method.
[0170] Embodiment 94. An embodiment in which the shaped abrasive particles have a two-dimensional shape of a partially concave triangle. 91. The abrasive article or method of embodiment 90.
[0171] Embodiment 95. The shaped abrasive particles have a length (Lb) of the body, a width (Wb) of the body, and a thickness (H) of the body. A body portion having a body thickness (Tb), Lb>Wb, Lb>Tb, and Wb>Tb. 91. The abrasive article or method of embodiment 90.
[0172] Embodiment 96. The body portion has a ratio of about 1:1 or more, or about 2:1 or more, or about 3:1 or more, or a first aspect ratio of about 5:1 or more, or about 10:1 or more and about 1000:1 or less. 96. The abrasive article or method of embodiment 95, having a to-to-f ratio (Lb:Wb).
[0173] Embodiment 97. The body portion has a ratio of about 1:1 or more, or about 2:1 or more, or about 3:1 or more, or a second aspect ratio of about 5:1 or more, or about 10:1 or more and about 1000:1 or less. 96. The abrasive article or method of embodiment 95, having a to-to ratio (Lb:Tb).
[0174] Embodiment 98. The body portion has a ratio of about 1:1 or more, or about 2:1 or more, or about 3:1 or more, or a third aspect ratio of about 5:1 or more, or about 10:1 or more and about 1000:1 or less. 96. The abrasive article or method of embodiment 95, having a to-to ratio (Wb:Tb).
[0175] Embodiment 99. The length (Lb), width (Wb), and thickness (Tb ) is about 0.1 microns or greater, or about 1 micron or greater, or about 10 microns or more, or about 50 microns or more, or about 100 microns or more, or About or greater than 150 microns, or greater than about 200 microns, or less than about 400 microns or greater than about 600 microns, or greater than about 800 microns, or greater than about 1 mm, And about 20mm or less, or about 18mm or less, or about 16mm or less, or about 14m m or less, or about 12 mm or less, or about 10 mm or less, or about 8 mm or less, or about 96. The abrasive article of embodiment 95 having an average dimension of 6 mm or less, or about 4 mm or less. Or a method.
[0176] Embodiment 100. The body portion is in a plane defined by the length of the body portion and the width of the body portion. For example, triangles, quadrilaterals, rectangles, trapezoids, pentagons, hexagons, heptagons, octagons, ellipses, Greek Spanish alphabet letters, Latin alphabet letters, Russian alphabet letters, and combinations thereof. Abrasive Article or Method.
[0177] Embodiment 101. The body portion is in a plane defined by the length of the body portion and the thickness of the body portion. In this case, triangles, quadrilaterals, rectangles, trapezoids, pentagons, hexagons, heptagons, octagons, ellipses, and Sha alphabet letters, Latin alphabet letters, Russian alphabet letters and combinations thereof. The abrasive article or method of
[0178] Embodiment 102. The body is a powder, a granule, a sphere, a fiber, a pore former, a hollow particle, or any of the above. 3. The abrasive article of claim 1 or 2, comprising a filler selected from the group consisting of a combination of Or methods.
[0179] Embodiment 103. The body is a wheel, a horn, a cone, a cup, a flanged wheel. , tapered cup, disk, sector, shaft tip, and combinations thereof. 3. The abrasive article or method of embodiment 1 or 2, having a shape. EXAMPLES
[0180] Example 1 6A and 6B show a conventional microcrystalline alumina grain (FIG. 6A) and an embodiment of the present invention. Scanning electron microscopy of a polished section of a representative nanocrystalline alumina grain (Fig. 6B). Scanning electron microscope (SEM) images are included. As shown, the average crystallite size of microcrystalline alumina (MCA) is The average crystallite size of nanocrystalline alumina (NCA) is approximately 0.2 microns. is approximately 0.1 microns.
[0181] Abrasive article samples containing nanocrystalline alumina were formed. A mixture containing abrasive particles, a binder, and an organic binder was prepared. The mixture was then mixed with different The mixture was then heat treated at 1260° C. to form an abrasive article. Sample S3 was formed by heat treating the sample at 915°C. Properties including modulus of rupture and elastic modulus were tested on samples S1, S2, and S3. As shown in FIG. 7A, sample S3 showed significantly higher oxidative stress than samples S1 and S2. Furthermore, as shown in FIG. 7B, sample S3 exhibited a higher modulus of rupture than sample S1. The elastic modulus of the fibrous tissue was significantly higher than that of S1 and S2.
[0182] Example 2 Two samples were obtained and tested for comparative purposes. The first sample (CS4) is a microcrystalline aluminum The second sample (S5) was a conventional vitrified grinding wheel with MCA. The vitrified grinding wheel was representative of the detailed embodiment. Sample CS4 had a surface roughness of about 0.2 microns. Sample S5 contained microcrystalline alumina with an average crystallite size of about 0.1 microns. The average crystallite size of each sample was 1.0 μm. was measured using the intercept method described herein. Samples CS4 and S5 were The same glass binder was used as shown in Table 1. Furthermore, samples CS4 and S5 were Abrasive particles of about 40% to 50% by volume of the total volume of the main body and the same content of bond It contains a material (approximately 10% to 15% by volume) and the same amount of pores (approximately 40% to 45% by volume). The sum of all components was equal to 100%. Samples CS4 and S5 had the same structure. The process was used to form the SiO2 thin film, both of which were formed at about 915°C.
[0183] [Table 1]
[0184] As shown in Figure 8, sample S5 was more stable during the external grinding test compared to sample CS4. The subjects showed significantly lower force thresholds.
[0185] Example 3 The Vickers hardness of representative MCA grain samples and NCA grain samples is shown herein. The MCA grains and NCA grains were measured according to the disclosed embodiment. The MCA grains were obtained from Cerpass ( Available under the trademark HTB. Nanocrystalline alumina and microcrystalline alumina. The crystallite sizes are approximately 0.1 and 0.2 microns, respectively. The NCA grain samples were prepared in the same way. Five samples of MCA and NCA grains were The Vickers hardness of the MCA grains and NCA grains was tested. Disclosed in 2.
[0186] The friability of NCA grains was measured according to the procedure disclosed herein. The NCA sample had a coarse grain size of 80, and the MCA grain was used as the reference sample. The milling time was 6 minutes. As shown in Table 2, the MCA grains had a friability of 10 The Vickers hardness of the NCA grains is very similar to that of the MCA grains. It exhibited a Vickers hardness of 123%.
[0187] [Table 2]
[0188] Embodiments of the present invention represent a departure from the state of the art. Crystalline alumina can be made to have an average crystallite size of less than a micron. However, those skilled in the art will appreciate that commercially available forms of microcrystalline alumina have a crystallinity of about 0.18 It is recognized that to the best of Applicants' knowledge, Currently, alumina-based abrasives with finer average crystallite sizes are not commercially available. In particular, the results for the abrasives containing NCA showed that the Vickers hardness of the MCA and NCA grains was significantly higher than that of the NCA grains. Given the finding that there is essentially no difference, this represents an extraordinary and unexpected result, and one of ordinary skill in the art would be able to One would not expect a significant difference in the performance of wheels using CA grains. The authors predict that NCA grains may be less effective in glass binders. This is because the more grain boundaries there are, the more likely the polishing grains will break apart. However, quite unexpectedly and unusually, the glass-bonded The abrasives made of nanocrystalline alumina grains form glass-bonded abrasives. Particular examples include glass-bonded polishing using MCA. It has been proven to be equivalent to or better than
[0189] Not all of the above operations in the general description or examples are required, but Some of the steps specified may not be required, and one or more additional steps may be added to the steps described. Note that additional actions may be performed in addition to the above. Furthermore, the order in which the actions are listed does not necessarily indicate the order in which they are performed. This is not the order in which they are presented.
[0190] Benefits, other advantages, and solutions to problems have been described above with regard to specific embodiments. while producing benefits, advantages, solutions to problems, and any benefits, advantages or solutions. Any feature which may enhance or make them more pronounced is set forth in any of the claims. should not be construed as indicating any or all essential, mandatory or essential features. stomach.
[0191] The details and explanations of the embodiments set forth herein are to be construed as general guidelines for the construction of various embodiments. The details and explanations set forth herein are intended to provide a thorough understanding of the present invention. A complete and comprehensive description of all elements and features of the apparatus and systems that use the structure or method being described. It is not intended to serve as a comprehensive description of the embodiments. In some embodiments, the invention may be provided in combination, whereas in others, the invention may be provided in combination, but for brevity, the invention may be provided in the context of one embodiment. The various features described in the present application may be provided separately or in any subcombination. Further, references to values stated in ranges include every value within that range. Many other embodiments may be apparent to those of skill in the art upon reading this disclosure. Structural, logical substitutions, or other changes may be made without departing from the scope of the present invention. Thus, other embodiments may be used and derived from this disclosure. The present disclosure should thus be regarded as illustrative rather than limiting. It is.
[0192] This Abstract of the Disclosure is provided for purposes of complying with patent laws and is not intended to provide a complete understanding of the scope of the claims or the principles of the present invention. are submitted with the understanding that they will not be used to interpret or limit the meaning of the terms and conditions set forth herein. Additionally, in the foregoing detailed description of the drawings, various features have been omitted for the purposes of streamlining the disclosure. The present disclosure may be grouped together or described in a single embodiment. It is contemplated that a claimed embodiment may require more features than are expressly recited in each claim. Rather, the following patents should not be construed as reflecting an intention to As the following claims reflect, the subject matter of the present invention encompasses all of the features of any of the disclosed embodiments. The claims below may be directed to less than one feature. The detailed description of the drawings, standing alone as separately defining the claimed subject matter, Can be incorporated.
Claims
1. 1. An abrasive article comprising a body portion, The main body portion is A binder including an inorganic material including ceramics; abrasive particles contained in the binder, the abrasive particles comprising nanocrystalline alumina having an average crystallite size of 0.09 microns or more and 0.14 microns or less; The main body portion is The abrasive particles are 40% to 65% by volume of the total volume of the body portion; The binder is 5% to 20% by volume of the total volume of the body portion; a porosity of 15% to 55% by volume of the total volume of the body portion; The nanocrystalline alumina includes an additive, the additive comprising: 2% to 8% by weight of the total weight of the nanocrystalline alumina 2 and, and MgO, which is 0.1% by weight or more and 5% by weight or less of the total weight of the nanocrystalline alumina; 2 The weight ratio of MgO to the total weight of the The abrasive article, wherein the abrasive particles are free of a β-alumina crystalline phase.
2. ZrO 2 2. The abrasive article according to claim 1, wherein the weight content ratio of MgO to MgO is 0.1 or more and 0.8 or less.
3. 10. The abrasive article of claim 1, wherein the nanocrystalline alumina has a density of at least 3.94 g / cc and up to 4.12 g / cc.
4. 4. The abrasive article of claim 1, wherein the body portion comprises a fixed abrasive article.
5. 4. The abrasive article of any one of claims 1 to 3, wherein the body portion has a shape including an abrasive wheel, a cone, a horn, a cup, a flanged wheel, a tapered cup, a segment, a shank end tool, a disk, a thin wheel, or a large diameter cut-off wheel.
6. 4. The abrasive article of claim 1, wherein the nanocrystalline alumina comprises from 51% to 99.9% by weight of alumina based on the total weight of the grain.
7. 4. The abrasive article according to claim 1, wherein the nanocrystalline alumina comprises additives in a total content of 0.1% by weight or more and 12% by weight or less of the total weight of the nanocrystalline alumina particles.
8. 4. The abrasive article of any one of claims 1 to 3, wherein the binder comprises a glass material having an amorphous phase, a non-glass material having a polycrystalline phase, or a combination thereof.
9. 1. An abrasive article comprising a body portion, The main body portion is A binder including an inorganic material including ceramics; abrasive particles contained in the binder, the abrasive particles comprising nanocrystalline alumina having an average crystallite size of 0.09 microns or more and 0.14 microns or less; The main body portion is The abrasive particles are 40% to 65% by volume of the total volume of the body portion; The binder is 5% to 20% by volume of the total volume of the body portion; a porosity of 15% to 55% by volume of the total volume of the body portion; The nanocrystalline alumina includes an additive, the additive comprising: 5% to 8% by weight of the total weight of the nanocrystalline alumina 2 and, and MgO, which is 0.1% by weight or more and 5% by weight or less of the total weight of the nanocrystalline alumina; 2 The weight ratio of MgO to the total weight of the The additive does not contain iron oxide; The abrasive article, wherein the abrasive particles are free of a β-alumina crystalline phase.
10. ZrO 2 10. The abrasive article of claim 1, 3, or 9, wherein the weight content ratio of MgO to MgO is 0.3 or more and 0.95 or less.
Citation Information
Patent Citations
Abrasive grains, abrasive articles and methods of making and using the same
JP2003510418A
Bonded polished articles and methods for forming them
JP2013512115A
Abrasive products containing abrasive particle materials, abrasive cloths and papers using abrasive particle materials, and forming methods
JP2014526395A
Abrasive particles, abrasive articles, and methods of making and using the same
US20130337725A1